Edukasi Penerapan Lingkungan Bersih dengan Memilah Sampah di SD Negeri Tlogo - Ni Luh Ardivta. S; Dita Nur Mala Sari; Nelly Syarifah Nur Aini; Lensy Wijaya sakti; Aqila Destiyana; Azwina Dira Sofia; Muhammad Farhan Febriansyah; Yulistya Indah Purwandari; sujono riyadi (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Background: In everything, of course, we cannot escape cleanliness, as we know that cleanliness is a reflection of health, especially environmental cleanliness, which is closely related to waste. Problems regarding environmental cleanliness that often occur are due to a lack of awareness about maintaining environmental cleanliness, so that an environment that is dirty due to littering results in several disasters such as floods during the rainy season, or the problem of waste being disposed of carelessly, causing clean water to become polluted. Method : This research at Tlogo State Elementary School uses a method of presenting material regarding waste sorting and how to protect the environment, with the target being that children in grade 3 at Tlogo State Elementary School can better understand the nature of waste that is easily decomposed or not easily decomposed. And a quiz or question and answer method with prizes regarding material related to the distribution of the characteristics of waste to measure the memory and intelligence of grade 3 children in tlogo state elementary schools. Results: This community service activity certainly produced maximum research and results, everything went very smoothly and the children at Tlogo State Primary School were very enthusiastic about answering questions. Even though the situation was chaotic for a moment because the children who were very active in class, 30% of them were not paying attention, were busy themselves and even fought. Then 70% pay attention, actively answer and follow the class well.